Cascade reemission of energy by inner-shell-ionized iron atom. (August 2022) - Kochur, A.G.; Chaynikov, A.P.; Dudenko, A.I.; Yavna, V.A.
Highlights: Cascade decays of vacancies in K, L and M shells of the Fe atom are simulated. Final ion charge spectra and the spectra of cascade electrons and photons are calculated. Large portion of energy transferred to ionized Fe atom is reemitted via cascade relaxation. Cascade relaxation is crucial in understanding the effect of ionizing radiation on matter. Abstract: Cascade decays of vacancies produced by single K, L and M ionization of the Fe atom are simulated by direct construction of the cascade decay trees based on Pauli–Fock branching ratios and ionic configurations energies. Final ion charge spectra and the spectra of cascade-produced electrons and photons are calculated. It is shown that a large portion of energy transferred to the Fe atom in the ionization processes is reemitted by cascade electrons and photons. This circumstance must be taken into account when describing the effect of ionizing radiation on matter or living tissues.